Comparative Analysis of Comedia Play of Ilocos Sur and Ilocos Norte - Adina, Theo Joshua P; Realgo, Bryan R (Integrated Journal for Research in Arts and Humanities, 2024)
Comedia, a traditional theatrical form in the Philippines, is a vibrant and colorful performance that blends comedy, drama, and music. Rooted in Spanish influences, particularly during the colonial period, Comedia has evolved into a distinct Filipino art form. This comparative study aimed to understand the similarities and distinctions between the Comedia plays of Ilocos Norte and Ilocos Sur. In collecting data, the researcher used techniques such as observation of the actual and retrieved recordings of the theatre play, interview techniques for the directors of both plays, and documentation. Meanwhile, in analyzing the data, the descriptive-comparative technique was used, namely, describing the data obtained in the field and analyzing it by looking for similarities and distinctions between the two research objects based on the elements of theater described by Aristotle, namely, plot, characters, theme, dialogue, music, and spectacle. While both provinces share fundamental elements of the Comedia, distinct variations emerge that reflect the unique cultural differences and influences of each locality. In Ilocos Norte, the Comedia play is modernized as it exhibits a fusion of romantic, comedic, and festive elements, with the incorporation of several characters, movements, props, and other elements. On the other hand, Ilocos Sur’s Comedia play is traditional as it showcases a blend of local traditions and Spanish influences, creating a performance that resonates with the province’s historical and cultural heritage.